Inhibition of Leishmania amazonensis arginase by fucogalactan isolated from Agrocybe aegerita mushroom - Motoshima, Renan Akio; Rosa, Tainara da F.; Mendes, Leia da C.; Silva, Estefania Viana da; Viana, Sthefany R. F. [UNESP]; Amaral, Bruno Sergio do; Souza, Dulce H. F. de; Liao, Luciano M.; Corradi da Silva, Maria de Lourdes [UNESP]; Sousa, Lorena R. F. de; Carbonero, Elaine R. (Elsevier B.V., 2018)
The inhibition of arginase from Leishmania spp. is considered a promising approach to the leishmaniasis treatment. In this study, the potential of a fucogalactan isolated from the medicinal mushroom Agrocybe aegerita was evaluated against arginase (ARG) from Leishmania amazonensis. The polysaccharide was obtained via aqueous extraction, and purified by freeze thawing and precipitation with Fehling solution. Its chemical structure was established by monosaccharide composition, methylation analysis, partial acid hydrolysis, and NMR spectroscopy. The data indicated that it is a fucogalactan (FG-Aa; M-w = 13.8 kDa), having a (1 -> 6)-linked alpha-D-Galp main-chain partially substituted in O-2 by non-reducing end-units of alpha-L-Fucp. FG-Aa showed significant inhibitory activity on ARG with IC50 potency of 5.82 +/- 0.57 mu M. The mechanism of ARG inhibition by the heterogalactan was the competitive type, with K(i)of 1.54 +/- 0.15 mu M. This is the first report of an inhibitory activity of arginase from L. amazonensis by biopolymers, which encourages us to investigate further polysaccharides as a new class of ARG inhibitors.
Keywords: Agrocybe aegerita; Fucogalactan; Chemical structure; Leishmania amazonensis; Arginase; Competitive inhibitor